BREEDING OF LOCAL GARLIC (Allium sativum L.) VARIETIES USING THE CHEMICAL MUTAGEN SODIUM AZIDE - Elok Faiqotus Zahro; Ni Wayan Deswiniyanti; Ni Kadek Dwipayani Lestari; Anak Agung Ayu Putri Permatasari; Ni Kadek Yunita Sari (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The demand for garlic in Indonesia continues to rise annually; however, the market remains dominated by imported garlic due to its larger bulb size compared to local varieties. One approach to improving the quality of local garlic is through mutation breeding using chemical mutagens such as sodium azide. This study aimed to evaluate the effects of sodium azide on morphological traits, stomatal index, and chlorophyll a and b content in local garlic (Allium sativum L.). The experiment was conducted using a Randomized Block Design (RBD) with a single treatment factor, sodium azide concentrations of 0.1%, 0.2%, 0.3%, and 0.4%. Observations revealed that the 0.4% concentration produced the best performance in plant height (24.20 cm), number of leaves (3.40), leaf length (22.10 cm), and leaf width (2.60 cm). The highest stomatal index (0.35) was also observed at this concentration. In contrast, the longest root length (2.320 cm) and highest fresh weight (0.8040 g) were found at the 0.3% concentration. The highest chlorophyll a and b content was recorded at the 0.1% concentration. These findings indicate that sodium azide induces significant variation in plant traits. Therefore, chemical mutagenesis is recommended as a promising breeding strategy to develop superior and competitive local garlic varieties.